ANALISIS EKONOMI USAHA PENGOLAHAN KERIPIK IKAN BAWIS (Siganus canaliculatus) PAK UCIL DI UMKM SAPUTRA SNACK KOTA BONTANG PROVINSI KALIMANTAN TIMUR - Reza Ramdhani; Helminuddin; Wahyu Fahrizal (2339-1324, 2021)
This research was aimed to calculate the economic performance of the Bawis fish chip processing business at UMKM Saputra Snack based on a feasibility analysis which includes; Revenue Cost Ratio (RCR), Break Event Points (Sales, Production, and Prices), Payback Period, and Return On Investment (ROI). This research was conducted in September 2020. Primary data was obtained through observation and interviews which were guided by a list of questions made according to the research objectives. Sample determination referred to the conditional/objective sampling method. The results show that the value of RCR is 3.55, the break-even point of sales is Rp. 1,259,607 per month, which is lesser than its actual sales of Rp. 18,000,000 per month; the breakeven point of production is 63 packs per month, which is lesser than the actual production of 900 packs per month; the breakeven price is Rp. 1,400 per pack which is lesser than the actual price of Rp. 20,000 per pack; the payback period is 1.41 months (0.12 years) and the result of ROI analysis shows a value of 71.10%. The results of the analysis of the overall economic performance show that the Bawis fish chip processing business at UMKM Saputra Snack is profitable and feasible to continue. Keyword: Bawis Fish Chips, Business Feasibility, Bontang.